Studi Kinerja Jalan Cipta Karya Kota Pekanbaru - Putra, M Riko; Djuniati, Sri; Elianora; Rurianti, Dwi Visti; Misriani, Merley; Marpaung, Horas Saut M (Teknik Sipil Universitas Riau, 2025)
Cipta Karya Street, located in Tampan District, Pekanbaru City, functions as a local road connecting HR. Soebrantas Street with Matoa and Cipta Karya Ujung Streets. This area experiences high vehicle density, contributing to congestion issues. A traffic volume survey was conducted at STA 00+100–00+300 on June 10, 13, and 15, 2024. The highest traffic volume was recorded on Monday, June 10, 2024, during peak hours (07.00–08.00 WIB) with 2,845 vehicles/hour or 1,235.2 pcu/hour. The side resistance value of 238.7 indicates a low level (L), while the road capacity is 1,442.5 pcu/hour. The free-flow speed of light vehicles was calculated at 33.81 km/hour. Based on the degree of saturation (DS) of 0.85, the road section performance is within acceptable limits according to PKJI (2014), indicating a stable traffic flow. However, the level of service (LOS) is classified as D, suggesting the flow is nearing instability, although the average speed remains above 25 km/hour. These findings highlight the need for traffic management strategies to prevent further decline in service level.